A novel Radio Frequency Identification three-dimensional indoor positioning system based on trilateral positioning algorithm. Issue 3 (September 2016) - Xu, He; Ding, Ye; Wang, Ruchuan; Shen, Weiwei; Li, Peng
GPS have been able to offer a commercially available outdoor positioning services; however, since the quality of satellite signals declines after entering into the indoor environment, the GPS system cannot provide indoor positioning services. With the development of cloud computing and the Internet of Things technology, indoor positioning has become a hot research hotspot. Radio Frequency Identification is a wireless communication technology, and the Radio Frequency Identification reader can communicate wirelessly through electromagnetic waves with the tag. Radio Frequency Identification technology has the following advantages: no contact, recognition from the long distance, long life and fast moving objects identification, etc. Radio Frequency Identification is the key component of Internet of Things, and many fusion application systems combining Radio Frequency Identification and cloud computing are emerging. This article designs and implements the Radio Frequency Identification indoor positioning system based on Received Signal Strength Indicator, which obtains three-dimensional coordinates orientation through multiple trilateral positioning algorithm on location tag. C# and Python are used to complete positioning system, where C# dominates user interface and calculates three-dimensional coordinates. Python is responsible for three-dimensional display. The two programs communicate through a socket.